Creative Building a Village By Empowering Technology as a Media of Information for The Community - Helmi Yazid; Dilla Ayu Ristanti; Hesti Widyani; Fikri Widyansyah; Alfina Bunga Assyaukanie; Muhamad Habib Anwar Fatwari; Alifia Nuraeni Mardini; Amsori Mahsusi; Muhammad Hafizh Fauzan (EQUATOR SINAR AKADEMIA, 2022)
Students as agents of change in society must be able to stimulate change through work programs made in Student Work Lectures (KKM). Much can be done to help and develop villages with work programs that are creative, simple, and easily understood by the village community. In particular, the current conditions that are happening in Indonesia, namely the Covid-19 pandemic and the emergence of the latest variant of Covid-19 are still the main problems. Thematic KKM activities are carried out online and offline, but most of the activities we do are online. With a series of programs to educate and socialize the community of Pasir Jaya Village regarding health issues, namely handling, prevention, transmission, and vaccination of Covid-19. Making the Desa Pasir Jaya website to serve as a medium for distributing information related to the village for its people, as well as providing a collaborative webinar with the 19,40,112 group, entitled